A conditional yeast mutant deficient in mRNA transport from nucleus to cytoplasm. - Tatsuhiko Kadowaki; Yang Zhao; Alan M. Tartakoff (1992)
Transport of mRNA from nucleus to cytoplasm is critical for eukaryotic gene expression; however, the mechanism of export is unknown. Selection and screening procedures have therefore been used to obtain a family of temperature-sensitive conditional mutants of Saccharomyces cerevisiae that accumulate poly(A)+ RNA in the nucleus when incubated at 37 degrees C, as judged by in situ hybridization. In one such mRNA transport mutant, mtr1-1, RNA synthesis continues, the export of poly(A)+ RNA is inhibited, intranuclear poly(A)+ is remarkably stable, and protein synthesis gradually stops. Thus, there is no tight coupling between RNA synthesis and export. The export lesion is reversible. Although mRNA export is clearly not a default option, neither inhibition of protein synthesis, inhibition of mRNA splicing, nor inhibition of poly(A)-binding protein function blocks export of the average poly(A)+, as judged by in situ hybridization. Further analysis of the family of mtr mutants should help map the path of RNA transport.